N-Acyldopamine induces aggresome formation without proteasome inhibition and enhances protein aggregation via p62/SQSTM1 expression - Gen Matsumoto (Nature Portfolio, 2018)
Abstract Accumulation of ubiquitinated protein aggregates is a common pathology associated with a number of neurodegenerative diseases and selective autophagy plays a critical role in their elimination. Although aging-related decreases in protein degradation properties may enhance protein aggregation, it remains unclear whether proteasome dysfunction is indispensable for ubiquitinated-protein aggregation in neurodegenerative diseases. Here, we show that N-oleoyl-dopamine and N-arachidonyl-dopamine, which are endogenous brain substances and belong to the N-acyldopamine (AcylDA) family, generate cellular inclusions through aggresome formation without proteasome inhibition. Although AcylDA itself does not inhibit proteasome activity in vitro, it activates the rearrangement of vimentin distribution to form a vimentin cage surrounding aggresomes and sequesters ubiquitinated proteins in aggresomes. The gene transcription of p62/SQSTM1 was significantly increased by AcylDAs, whereas the transcription of other ubiquitin-dependent autophagy receptors was unaffected. Genetic depletion of p62 resulted in the loss of ubiquitinated-protein sequestration in aggresomes, indicating that p62 is a critical component of aggresomes. Furthermore, AcylDAs accelerate the aggregation of mutant huntingtin exon 1 proteins. These results suggest that aggresome formation does not require proteasome dysfunction and AcylDA-induced aggresome formation may participate in forming cytoplasmic protein inclusions.